1952
DOI: 10.1002/jsfa.2740030409
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine‐producing bacteria in whalemeat

Abstract: The ability of organisms isolated from the flora of whalemeat to produce trimethylamine from trimethylamine oxide, choline and lecithin has been investigated with reference t o the production of ' fishy ' flavours. More than half produced it from trimethylamine oxide, one-eighth from choline and none from lecithin. It is not decided how far this may be significant in commercial practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1952
1952
1971
1971

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…At all 3 temperatures after initial increases in concentration, which the authors suggested was the result of meat arginase activity, there was a decrease which occurred during the logarithmic phase of bacterial growth. I n whalemeat, there are appreciable proportions of trimethylamine oxide which is readily attacked by various bacteria occurring in or on chilled whalemeat liberating trimethylamine, thus giving a characteristic fishy smcll to meat of this kind (Robinson, Ingram & Eddy, 1952).…”
Section: (Ii) Induced Chemical Changesmentioning
confidence: 99%
“…At all 3 temperatures after initial increases in concentration, which the authors suggested was the result of meat arginase activity, there was a decrease which occurred during the logarithmic phase of bacterial growth. I n whalemeat, there are appreciable proportions of trimethylamine oxide which is readily attacked by various bacteria occurring in or on chilled whalemeat liberating trimethylamine, thus giving a characteristic fishy smcll to meat of this kind (Robinson, Ingram & Eddy, 1952).…”
Section: (Ii) Induced Chemical Changesmentioning
confidence: 99%